PLASTY OF DURA MATER DEFECTS BY COLLAGEN IMPLANTS USING NON-SUTURE CONTACT DIRECT BONDING METHOD - D. E. Alekseev; D. V. Svistov; D. E. Matsko; E. D. Alekseev (Вестник хирургии имени И.И. Грекова)
OBJECTIVE. The study investigated and compared the efficacy of plasty of dura mater using different collagen materials in the experiment. MATERIALS AND METHODS. The experimental study in vivo was carried out on 60 laboratory animals. Rabbits were divided into 4 groups after performing the craniotomy and dura mater opening. It depended on the material used for plasty of dural defects such as Duraform, Lyostypt and Russian prototype of collagen matrix for dural grafting. The fourth group was the control group. The presence and severity of meningo-cerebral adhesion, histological and immunological researches of duraplasty areas were performed after the experiment. RESULTS. The severity of meningo-cerebral adhesion was significantly higher in control group, but there wasn’t noted any meaningful difference in the groups with different collagen matrices. These groups had similar histological and immunohistochemical features. CONCLUSIONS. An application of collagen matrix improved the results of duraplasty and prevented formation of meningo-cerebral adhesions in the experiment. This data predict the high clinical efficacy of the method.